2017
DOI: 10.3390/nu9070706
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Leukoprotease Inhibitor (Slpi) Expression Is Required for Educating Murine Dendritic Cells Inflammatory Response Following Quercetin Exposure

Abstract: Dendritic cells’ (DCs) ability to present antigens and initiate the adaptive immune response confers them a pivotal role in immunological defense against hostile infection and, at the same time, immunological tolerance towards harmless components of the microbiota. Food products can modulate the inflammatory status of intestinal DCs. Among nutritionally-derived products, we investigated the ability of quercetin to suppress inflammatory cytokines secretion, antigen presentation, and DCs migration towards the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Host polymorphisms in ubiquitin proteasome system genes have been associated with the risk of IBD 57. This is relevant considering that both microbiota-based58 and non-microbiota-59 60based inhibition of protease activity has been investigated. We also showed that intestinal permeability is higher in mice humanised with high PA stool suggesting that microbiota may regulate intestinal permeability via ineffective inhibition or production of specific intestinal proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Host polymorphisms in ubiquitin proteasome system genes have been associated with the risk of IBD 57. This is relevant considering that both microbiota-based58 and non-microbiota-59 60based inhibition of protease activity has been investigated. We also showed that intestinal permeability is higher in mice humanised with high PA stool suggesting that microbiota may regulate intestinal permeability via ineffective inhibition or production of specific intestinal proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, one of the most common flavonoids present in vegetables and fruits, has been reported to be an anti‐inflammatory substance that possesses a strong anti‐inflammatory ability . This function has been studied in different cell types, in both animal and human models . Additionally, recent work has clearly demonstrated quercetin immunosuppressive effects on dendritic cells function .…”
Section: Discussionmentioning
confidence: 99%
“…DCs line the gastrointestinal tract epithelial monolayer, continuously sampling the intestinal lumen to present luminal antigen and trigger the adaptive immune response . Intestinal DCs respond to quercetin oral administration by initiating an anti‐inflammatory molecular pathway . Here we demonstrate that miR‐369‐3p is also induced by intestinal resident DCs.…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, our groups, together with several others worldwide, demonstrated the ability of nutritionally derived bioactive compounds to suppress inflammatory cytokine release (40)(41)(42)(43). In particular, the administration of several plant-derived polyphenols to in vitro cultured immune cells suppressed the release of inflammatory cytokines (44).…”
Section: Can Nutritionally Derived Products Help To Contain/alleviatementioning
confidence: 99%